Alat Monitoring Suhu Melalui Aplikasi Android Menggunakan Sensor LM35 dan Modul SIM800L Berbasis Mikrokontroler ATMega16 - Sawita, I Kadek Agus Sara; Supardi, I Wayan; Putra Adnyana, I Gusti Agung (BULETIN FISIKA; Vol 18 No 2 (2017): BULETIN FISIKA, 2017)
It has been successfully designed a temperature monitoring instrument through android application using LM35 sensor and SIM800L module based on ATMega16 microcontroller. The temperature is measured using a LM35 sensor which produces a voltage and sent to ADC. Microcontroller ATMega16 is using as the main processor of this monitoring instrument to calculate the program, so that analog data in the form of input voltage are converted into digital data form a measurable temperature. The measurable temperature is sent and saved in the database on the server computer using the SIM800L module so it can be displayed on the website. The website pages are accessed with android programs that installed on the smartphone so that measurable temperature data can be monitored using a smartphone. The measurable temperature results can be displayed on a 2x16-character LCD in the instrument designed. Compatibility of monitoring instrument with comparison instrument is 99,97 %.